2015
DOI: 10.1159/000371898
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorenal Syndrome Type 1: A Defective Regulation of Monocyte Apoptosis Induced by Proinflammatory and Proapoptotic Factors

Abstract: In this study, we examined the possible immune-mediated mechanisms in cardiorenal syndrome (CRS) type 1 pathogenesis. We enrolled 40 patients with acute heart failure (AHF), 11 patients with CRS type 1 and 15 controls. Plasma from the different groups was incubated with monocytes; subsequently, cell apoptosis was evaluated by DNA fragmentation, caspase activity and cytofluorometric assay. Cytokine quantification in plasma and supernatant was performed by ELISA. Monocytes treated with CRS type 1 plasma showed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 30 publications
3
25
0
Order By: Relevance
“…Activation of the immune and cellular response, inflammation, oxidative stress, and activation of apoptotic pathways are involved in the pathogenesis of CRS1 [7,9,10,11,12,13]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Activation of the immune and cellular response, inflammation, oxidative stress, and activation of apoptotic pathways are involved in the pathogenesis of CRS1 [7,9,10,11,12,13]. …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have specifically shown that apoptosis is implicated in CRS1 pathogenesis [11,12]. These findings suggest the presence of proinflammatory cytokines and proapoptotic factors in CRS1 plasma that induce a defective regulation of monocyte apoptosis in such patients [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…play an important role in innate and adaptive immune responses to CRS. In particular, experimental data demonstrated that a defective regulation of monocyte apoptosis and an immune-mediated mechanism play a fundamental role in the pathophysiology of type 1 CRS [75]. …”
Section: Can Ecs Function As Antigen-presenting Cells In Crs?mentioning
confidence: 99%
“…Recently, considerable attention has been paid to the role of new alternative mechanisms, such as epigenetics, prenatal programming, small noncoding RNAs, and extracellular vesicles, which may be part of the pathogenesis of cardiorenal cross-talk [11, 12]. Recent data suggest that both tubular epithelial cells and monocytes, when exposed to plasma of patients with CRS type 1, increase cell apoptosis (DNA fragmentation and augmented caspase activity) and cytokine production (IL-6 and IL-18) [7, 12]. Furthermore, higher levels of reactive oxygen species and reactive nitrogen species production were detected in the plasma of CRS type 1 patients when compared to acute heart failure (AHF) patients [6].…”
Section: Introductionmentioning
confidence: 99%